THE RACE TOWARD ‘ETHICALLY UNIVERSALLY ACCEPTABLE’ HUMAN PLURIPOTENT (EMBRYONIC-LIKE) STEM CELLS: ONLY A PROBLEM OF SOURCES? - Neri, Demetrio (Bioethics, 2011)
Over the past few years, several proposals aimed at procuring human pluripotent (embryonic-like) stem cells without involving the destruction of a human embryo have been proposed and widely discussed. This article focuses on a basic aspect of the debate, namely the plausibility of one or more of these new proposals being able to meet the ethical requirements that those who regard the human embryo as sacred have tried to impose on stem cells research in the last ten years. The thesis of the article is that focusing the discussion only on the sources of stem cells has prevented a full understanding of the foundation, meaning and scope of these ethical requirements. To substantiate this thesis, the article takes into consideration two issues: the first has to do with the potential of the cells obtained through some of the new approaches (iPS included), the second (and decisive) with the argument of the ‘indirect complicity’, applied to the use of ‘contaminated’ knowledge.